Penguatan Perencanaan Keuangan Keluarga pada Pengusaha Kuliner Kawasan Gasibu Mini Antapani Kulon Kota Bandung - Bramasto, Ari; Oktavian, Rizky Ferari; Anggadini, Sri Dewi (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
Abstract Culinary entrepreneurs in the Gasibu Mini, Bandung, don't have much knowledge about family financial management, don't know much about capital investment, and need insight into capital investment. The fact of life is limited not only today, but it is necessary to think about the future too. Hope for the future will improve, many things in life need to be planned as well as possible, this is also the case with family financial planning. Financial planning for culinary entrepreneurs in Gasmin area does not need to be too complicated. Financial planning is carried out by making expenditure and income in detail. It is also necessary to pay attention to the regularity and neatness of recording so that the family's financial condition can be measured and is able to show whether the family's financial condition is healthy or whether they are experiencing problems. Financial planning is used as a strategy for separating family capital and business capital as an effort to increase efficiency. The aim of PkM activities is to ensure that families of culinary entrepreneurs have clear steps in mapping out financial planning for the future. The implementation method in solving problems is through socializing the importance and use of family financial planning, assistance in using capital investment and other alternatives, continuous assistance for 3 months which in the end can set aside 30% of total income for a better future. Mandatory outputs include publications through journals and news as well as online videos